Comprehensive Physiology 2013
DOI: 10.1002/cphy.c130007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Freezing Tolerance

Abstract: Winter survival for many kinds of animals involves freeze tolerance, the ability to endure the conversion of about 65% of total body water into extracellular ice and the consequences that freezing imposes including interruption of vital processes (e.g., heartbeat and breathing), cell shrinkage, elevated osmolality, anoxia/ischemia, and potential physical damage from ice. Freeze-tolerant animals include various terrestrially hibernating amphibians and reptiles, many species of insects, and numerous other invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 228 publications
2
150
1
Order By: Relevance
“…Water will thus change from liquid to solid state and form ice crystals in the extracellular space, increasing even more the osmolarity of the extracellular space 28 . Since glycerol is toxic, a controlled flow of this molecule over the plasma membrane is required in order for the cells to survive, a matter that is controllable at low (5°C) temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Water will thus change from liquid to solid state and form ice crystals in the extracellular space, increasing even more the osmolarity of the extracellular space 28 . Since glycerol is toxic, a controlled flow of this molecule over the plasma membrane is required in order for the cells to survive, a matter that is controllable at low (5°C) temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly, work on short-term cold shock gene expression changes has shown that the predominant group of genes showing expression changes are those involved in the stress and immune response (e.g. heat shock proteins (Hsps), Turandot genes, etc) (Zhang et al, 2011;Sinclair et al, 2013;Storey and Storey, 2013). In addition, the neuropeptide CAPA has been shown to play an important role in both cold and desiccation resistance in several species of Drosophila, including D. montana, when assessed using cold shock (Terhzaz et al, submitted).…”
Section: Functional Processesmentioning
confidence: 99%
“…With the predicted increase in global temperatures, and their potential impact on agricultural productivity, there are efforts to understand the genetic basis of temperature responses in plants. Traditionally, temperature effects have been studied in the context of extreme stress responses such as heat shock or cold shock (Kotak et al, 2007;Barrero-Gil and Salinas, 2013;Song et al, 2013;Storey and Storey, 2013). In recent times, there has been an interest in analyzing the response of plants to changes in their growth temperature within the nonstress range of l6°C to 27°C, as even small changes in temperature can have major impacts on plant growth and development (Wigge, 2013;Franklin et al, 2014).…”
mentioning
confidence: 99%